Hubungan faktor determinan dengan penggunaan kontrasepsi pada wanita usia ASFR (Age Spesific fertility Rate) - Nilawati, .; Umboh, Adrian; Tendean, Lydia (UNIVERSITAS SAM RATULANGI, 2020)
Abstract: This study was aimed to Determinant Factors in the Use of Contraception in Women Age ASFR (Age Specific Fertility Rate) in the Province of North Sulawesi. The population is all women aged in ASFR in North Sulawesi. Sampling based on raw data SKAP adjusted to the inclusion and exclusion criteria. Â Analysis with Chi Square test and Logistic regression. The results of the study found a relationship between education, family planning counseling service and family planning service, while the number of children, residential areas and the mass media were not. Based on multivariate results, family planning counseling service have a large role which is obtained OR value of 25.078 (95% CI = 3.089-203.625). Conclusion, education, family planning services counseling and family planning services have a significant relationship, while the number of children, residential areas and the mass media were not.Keywords: determinants factors, education, children, residential area, mass media, family planning, counseling, service, women age ASFRÂ Â Abstrak: Tujuan penelitian ini adalah mengetahui faktor determinan penggunaan kontrasepsi pada wanita usia ASFR (Age Specific Fertility Rate) di Provinsi Sulawei Utara. Jenis penelitian analitik dengan desain cross-sectional. Populasi semua wanita usia ASFR di Provinsi Sulawesi Utara. Pengambilan sampel berdasarkan raw data SKAP yang disesuaikan dengan kriteria inklusi dan eksklusi. Analisis dengan uji Chi Square dan regresi Logistic. Hasil penelitian terdapat hubungan antara pendidikan, konseling pelayanan KB dan tempat pelayanan KB sedang jumlah anak, wilayah tempat tinggal dan media massa tidak. Berdasarkan hasil multivariate konseling pelayanan KB mempunyai peran yang besar dimana di peroleh nilai OR 25,078 (CI 95% = 3,089-203,625). Kesimpulan pendidikan, konseling pelayanan KB dan tempat pelayanan KB mempunyai hubungan yang signifikan, sedangkan jumlah anak, wilayah tempat tinggal dan media tidak.Kata kunci: faktor determinan, pendidikan, jumlah anak, daerah pemukiman, media massa, konseling, pelayanan, keluarga berencana, wanita usia ASFR.